First-Principles Study on Various Point Defects Formed by Hydrogen and Helium Atoms in Tungsten - Qiang Zhao; Zheng Zhang; Yang Li; Xiaoping Ouyang (Science and Technology of Nuclear Installations)
The different point defects formed by two hydrogen atoms or two helium atoms in tungsten were investigated through first-principles calculation. The energetically favorable site for a hydrogen atom is tetrahedral interstitial site while substitutional site is the most preferred site for a helium atom. The formation energies of two hydrogen or helium atoms are determined by their positions, and they are not simply 2 times the formation energy of a single hydrogen or helium atom’s defect. After relaxation, two adjacent hydrogen atoms are away from each other while helium atoms are close to each other. The reasons for the interaction between two hydrogen or helium atoms are also discussed.